Determinants of domestic and cross-border bank acquisitions in the European Union - Ignacio Hernando; María J. Nieto; Larry D. Wall (Federal Reserve Bank of Atlanta, 2008)
This paper analyzes the determinants of bank acquisitions both within and across 25 members of the European Union (EU-25) during the period 1997-2004. Our results suggest that poorly managed banks (those with a high cost-to-income ratio) and larger banks are more likely to be acquired by other banks in the same country. The probability of being a target in a cross-border deal is larger for banks that are quoted in the stock market. Finally, banks operating in more concentrated markets are less likely to be acquired by other banks in the same country but are more likely to be acquired by banks in other EU-25 countries.
Keywords: G21; G34; 330; bank acquisitions; merger gains; probability of acquisition; Internationale Bank; Übernahme; Ausländisch; Bank; EU-Staaten